2018
DOI: 10.20961/ijie.v2i2.25504
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effect of Developed Reader Response Strategy-Based Mobile Reading for Students’ Establishing Character and Comprehension Achievement

Abstract: Mobile learning is nowadays utilized by educators to meet the students’ mode of learning in this digital era. This current study’s objective is to develop the mobile learning of reading based reader response strategy for comprehension achievement and character establishment of the eleventh grade students of SMAN 4 Lubuklinggau with 29 student. By employing development research with Analysis, Design, Development, Implementation, and Evaluation (ADDIE) research design , reading test material was delivered to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Developing materials has caught the attention of a plethora of researchers. Some studies had been conducted by Inderawati et al (2018), Mahardika (2018), Erfiani et al (2019), Monica and Vianty (2019), Sopian et al (2019), Elviana et al (2020), Nafiah (2020, and Surdyanto and Kurniawan (2020). Those previous studies aimed to develop materials for EFL classes, especially for reading materials.…”
Section: Introductionmentioning
confidence: 99%
“…Developing materials has caught the attention of a plethora of researchers. Some studies had been conducted by Inderawati et al (2018), Mahardika (2018), Erfiani et al (2019), Monica and Vianty (2019), Sopian et al (2019), Elviana et al (2020), Nafiah (2020, and Surdyanto and Kurniawan (2020). Those previous studies aimed to develop materials for EFL classes, especially for reading materials.…”
Section: Introductionmentioning
confidence: 99%
“…It was because technology had an important role in promoting activities for learners and a significant effect on teachers' teaching methods. Similarly, Inderawati, Agusta, and Sitinjak (2018) found that mobile learning as one of the modes of learning had a potential effect on students' reading achievement.…”
Section: The Way Of English Education Students Obtain Tpack In Learningmentioning
confidence: 95%
“…The quality of books on the market does not fully meet students' needs, stressing the task of supplying knowledge or facts alone (Wena, 2014). Many researchers are interested in developing reading materials (Azizah et al, 2021;Elviana et al, 2020;Inderawati et al, 2018;Mahardika, 2018;Nafiah, 2020;Sopian et al, 2019). Previous studies aimed at developing EFL teaching materials, particularly reading resources.…”
Section: Introductionmentioning
confidence: 99%